Coupling noble gas and alkane gas isotopes to constrain normally pressured shale gas expulsion in SE Sichuan Basin, China - Li, Jiaxin; Wang, Yunhai; Fang, Dazhi; Wen, Zhigang; Wu, Chenjun (Frontiers in Earth Science, 2024)
The molecular and isotopic compositions of shale gases exhibit substantial differences under different storage conditions. Gas geochemistry is widely used when evaluating gas accumulation and expulsion in petroleum systems. Gas geochemical characteristics can provide important references for determining the enrichment mechanism of shale gas reservoirs and predicting shale gas production capacity in different regions. In tectonically stable regions with similar reservoir formation and evolution histories, shale gas reservoirs are expected to exhibit favorable storage conditions with only relatively small variations in gas geochemical characteristics. In tectonically active regions, shale gas preservation conditions are expected to be more variable. In this study, we systematically analyzed the stable isotope signatures (δ13C and δD) of alkane gases (CH4, C2H6, and C3H8), along with noble gas compositions and isotopic signatures, of normally pressured Wufeng‒Longmaxi marine shale gas samples comprising a continuous pressure coefficient series from a structurally active region at the transition between an orogenic belt and the southeastern (SE) Sichuan Basin, China. The relationships between noble gas contents, isotopic signatures, and shale gas yields were evaluated, and a mechanism for normally pressured shale gas accumulation and expulsion was presented. The δ13C and δD data suggest that the normally pressured shale gas originated from late-mature thermogenic generation, equivalent to shale gas from other production areas in the inner Sichuan Basin. Gas dryness ratios [C1/(C2 + C3)] exhibit negative relationships with δ13C1 and δ13C2. Normally pressured shale gas yields exhibit a negative correlation with δ13C and a positive correlation with [C1/(C2 + C3)], suggesting differences in shale gas accumulation and expulsion across the studied region related to changes in the pressure coefficient. Noble gas isotope data suggest that the normally pressured Longmaxi shale gas received a substantial contribution of crust-derived He. Coupling noble gas and stable C/H isotope data reveals that the abundance of He and Ar, along with the δ13C signatures of alkane gases, is affected by the abundance of shale gas during the accumulation and expulsion process. The noble gas and stable isotope distribution trends presented herein can be used to evaluate Wufeng‒Longmaxi’s normally pressured shale gas accumulation and expulsion in complex structural areas of the southeastern Sichuan Basin. Better preservation conditions accompanying lower tectonic activity will normally result in higher shale gas production and a lower concentration of noble gases. The above findings show that gas geochemical characteristics could be used as effective evaluation indicators for determining shale gas accumulation mechanisms in tectonically active regions.